Alimony payment agreement: problems of theory and practice - Shadanova, L.Zh. (Bulletin of the Karaganda University “Law Series”, 2023)
The article is devoted to the study of the legal nature of the alimony payment agreement as a civil transaction between the alimony payer and the alimony recipient. The alimony payment agreement is concluded out of court and the norms of the Civil Code of the Republic of Kazakhstan and apply to the conclusion, execution, modification, termination and invalidation of the alimony payment agreement. The article discusses the theoretical and practical problems of legal regulation of the institution of an agreement on the payment of alimony. The essential conditions of the alimony contract, the procedure for concluding, changing, and terminating the contract are analyzed. Attention is focused on the problems of defining the concept of an agreement on the payment of alimony, the legal nature of the contract, the definition of the actual parties to the agreement, the legal status of the legal representatives of the parties. The purpose of the study is to study the theory and analysis of the legal norms governing the conclusion of an agreement on the payment of alimony, notarial practice for the certification of this agreement and judicial practice for the consideration of disputes related to the contestation, modification, termination, execution of this agreement. As a result, the author gives his own definition of the concept of an agreement on the payment of alimony as a civil transaction concluded between a person obliged to pay alimony and a recipient of alimony on the amount, conditions, procedure and method of payment of alimony.